Best Answer

(4x - 3y)(16x^2 + 12xy + 9y^2)

User Avatar

Wiki User

โˆ™ 2015-09-26 01:03:49
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How do you factor 64x to the third power minus 27y to the third power?
Write your answer...
Related questions

Factor 64x to the third power minus 27x to the third power?

In case you meant 64x^3 - 27y^3, that factors to (4x - 3y)(16x^2 + 12xy + 9y^2)

How do you factor 8xยณ-27yยณ?


What is the gcf of 27y and 54y3?

Since 27y is a factor of 54y3, it is automatically the GCF.

Which is the common factor of the expression 6y2 27y?

It is: 3y and y

Factor 9x-27y by separating the GCF?

9(x - 3y)

How do you factor y cubed plus 27z cubed?

(y + 27)(y^2 - 27y + 729)

What is the least common multiple of 27y and 54y3?

Since 54y3 is a multiple of 27y, it is automatically the LCM.

What is the LCM 63x and 27y?


27y squared plus 42y-5?

Reorder the terms: -5 + 42y + 27y2 Factor a trinomial. (-5 + -3y)(1 + -9y)

What is y plus 3 to the third power plus 2 divided by 4?

It depends on where there are parentheses, if there are any. y + 33 + 2/4 = y + 27.5 (y+3)3 + 2/4 = y3 + 9y2 + 27y + 27.5

Simplify the expression 32y - 5y?


What is the factor of 14y 28y-54y?

2(7y + 14y - 27y)or you could just total them-1 x 2 x 2 x 3 x y = -12y

3sq root -27y36 over 1000?

~(3)-27y=(36)/(1000)Reduce the expression (36)/(1000) by removing a factor of 4 from the numerator and denominator.~(3)-27y=(9)/(250)Since ~(3) does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting ~(3) from both sides.-27y=-~(3)+(9)/(250)Divide each term in the equation by -27.-(27y)/(-27)=(-~(3)+(9)/(250))/(-27)Simplify the left-hand side of the equation by canceling the common terms.y=(-~(3)+(9)/(250))/(-27)Simplify the right-hand side of the equation by simplifying each term.y=(250~(3)-9)/(6750) y=0.06

Who is the short haired female dancer in Justin Timberlake's My Love video?

tammy fey from mesquite,texas. 27y/o

How do you factorise 15x-27xy?

Factorising 15x-27xy gives 3x (5 - 9y).Factorising is to express a number or expression as a product of factors.When factorising always look for common factors. To factorise (15x-27xy) look for the highest factor between the two terms (3x). 15x - 27y = 3x (5 - 9y)

How do you solve this problem 5 times 3y plus 1 plus 12y-1?

5*3y+1+12y-1 = 15y+1+12y-1 = 27y.

Solve 27y plus 18x equals 21?

This can be interpreted as a line in 2d space. There are an infinite number of solutions. More than likely your real question is: "How can 27y + 18x = 21 be written in standard slope-intercept form?"Same as 9y + 6x = 7 (divide both sides by 3).Solve for y:9y = 7 - 6xy = (7 - 6x) / 9, ory = (-2/3)x + 7/9We now have an eaquation of a line: slope = -2/3, y-intercept = 7/9Paste -2/3x + 7/9 into the calculator at click "Eval" to visualize it.

What is the smallest positive integer n such that 2n is a perfect square and 3n is a perfect cube?

n=72 satisfies the relation. 2*72 = 12**2, and 3*72 = 6**3. The only question is whether or not that is the smallest integer that will do so. All perfect squares of which 2n is a factor are of form (2x)**2 = 4x**2, with n= 2x**2. Similarly all perfect cubes of which 3n is a factor are of form (3y)**3 = 27y**3 with n = 9y**3. So, we need integers x and y such that 2x**2 = 9y**3. If the integers x and y are the smallest that satisfy the equation, then we have the smallest n. It doesn't work for y = 1, or any other odd number. If y = 2, n = 72. There is a number x =6 which satisfies the relation. Since y is smallest possible, then n=72 is the smallest positive integer that satisfies the relation.

10x plus 9y equals 4 and -6x plus 4y equals -5?

Multiply first equation by 3 and second equation by 5:30x + 27y = 12, -30x + 20y = -25; add these two:47y = -13, making y = -13/47 and x = -61/94I have checked these values against the original equations and they satisfy both. Weird solution tho'!

How do you find a product of a cube of a binomial?

There is a trick to this one. cube the first and write it down. write the opposite sign of the middle term. multiply the first constant times the second constant times 2 and write it down. square the first term write it down, square the second term and write it down. cube the last term including its sign and write it down. Example: (a-b)^3= a^3+2a^2b^2-b^3 (2x+3y)^3=8x^3=12x^2y^2+27y^3

What is the completely factored form of the expression 27y cubed minus1?

Fortunately, one of the three roots of 27y3 - 1 is really obvious, y = 1/3. Therefore we can pull (y - 1/3) out of the expression giving us:(y - 1/3)(27y2 + 9y +3).Using the quadratic formula on the second multiplicative expression gives:[-9 ± √(-243)]/54 = (-9 ± 9i√3)/54.So the complete, factored form of 27y3 - 1 is:(y - 1/3)[y - (9 + 9i√3)/54][y - (9 - 9i√3)/54].

How do you find graph cordinates in this problem 5x-9y equals 43 3x plus 8Y equals 68?

5x - 9y = 43 (A)3x + 8y = 68 (B)(A)*3: 15x - 27y = 129(B)*5: 15x + 40y = 340Subtracting the first from the second gives67y = 211 => y = 211/67 = 3.15 approxSubstituting the [rational] value of y in (B)5x - 9*211/67 = 43 => 5x = 43 + 1899/67 = 4780/67therefore x = 956/67 = 14.27 approx.

Suppose that y varies directly as the cube of x If x is tripled what is the effect on y?

y will be multiplied by 27. Remember, whatever you do to one side of an equation, you must do to the other. In this case, the relationship between x and y would be expressed as y = x^3 To triple x would look like y = (3x)^3 ...b/c you're tripling the value x alone, not the entire term x^3 y = 27x^3 ...after distributing the exponent (3^3 = 27) In order to set both sides of the equation equal, y must be multiplied by 27... 27y = 27x^3 TADA!

How do you solve the system of equation using substitution problem for 5x-2y equals 4 and x plus 5y equals 0?

5x - 2y = 4 [1] x + 5y = 0 [2] Substituting x into 1st equasion, by re-arranging 2nd: x + 5y = 0 x = -5y 5(-5y) - 2y = 4 -25y - 2y = 4 -27y = 4 y = -4/27 x = -5y x = -5(-4/27) x = 139/27 note: in most cases you will need to simplify the fraction. not in this case, this is an unlikely sum, usually given by an out of school tutor or there is an error with your reading of the question, usually the answers are better fractions.

If 3x equals 7y-2 and 9y equals 4x plus 1 Then what is the value of x and y?

3x = 7y - 2 (subtract 3x and 7y to both sides of the first equation)9y = 4x + 1-7y = -3x - 2 (multiply by 4 each term of both sides of the first equation)9y = 4x + 1 (multiply by 3 each term of both sides of the second equation)-28y = -12x - 827y = 12x + 3 (add both equations)-y = -5 (multiply by -1 both sides)y = 53x = 7y - 2 (substitute 5 for y)3x = 7(5) - 23x = 33 (divide both sides by 3)x = 11Thus, the solution of the given system of the equations is x = 11 and y = 5.

People also asked

What is the significance of the twelve tables in roman law?

View results

Oppress in a sentence?

View results

What is the rising action of the Edgar Allan Poe's story The Masque of the Red Death?

View results

Who are the characters of the masque of the red death?

View results

Climax of the masque of the red death?

View results

What is the setting for The Masque of the Red Death?

View results